EFEKTIVITAS DAN KAPASITAS RESIN PENUKAR ANION DENGAN SISTEM BATCH DALAM MENGIKAT NITRAT DAN APLIKASINYA PADA AIR DARI SUMBER MATA AIR DI DESA SEDANG - A.A. Bawa Putra (Master Program of Environmental Science, Postgraduate Program of Udayana University)
It has been conducted a research concerning efficiency and capacity of anion resin changing in batchsystem to nitrate. The subsequent tools designs are applied to decrease nitrate level to the water source atSedang Village. Nitrate level analysis applies spectrophotometer ultraviolet-visible.The result of research shows that resin is able to decrease nitrate level beyond Water QualityStandard of Group B in its effectiveness between 99.98% - 99.99%, meanwhile its capacity is at 0.3608 mg/gin concentrated period of 190 minutes.The measurement of water sources in Sedang Village shows that these water sources have beenpolluted by nitrate (up to Water Quality Standard of Group B) for the level between 13.9212 ppm – 19.5920ppm. The usage of resin is able to decrease level of nitrate in water coming from these water sources to theirbelow level of Water Quality Standard.